Development of Interactive Learning Application “Smart Educa” as Learning Media for Introductory Business Courses - Umatin, Choiru; Heri Pratikto; Wening Patmi Rahayu (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this research is to develop an interactive learning application based on Android and Desktop "Smart Educa" as a learning media for Introduction to Business courses. The research method used in the development of this interactive learning application is development research with the ADDIE method (Analysis, Design, Development, Implementation and Evaluation). Measuring the ease of use of the application and user feedback on the "Smart Educa" application involved 50 2nd semester students of the Introduction to Business course at IAIN Kediri's Sharia Economics Study Program as respondents selected based on proportional stratified random sampling techniques. The test results show that the assessment of students from various aspects obtained an average value of 2.99 which is included in the feasible category.